The Role And Place Of Library And Information Institutions In The Formation Of A Culture Of Reading - Nosirov, Uktam; Davlatov, Soyibnazar; Urozov, Abdurasul (The journal of contemporary issues in business and government, 2021)
This article analyzes the role and place of library and information institutions in the formation of a culture of reading. Information on the formation of a culture of reading and information culture around the world, its importance in the life of society is published with different approaches. All this is due to a person's interest in various fields of knowledge and the ability to quickly find and learn what is necessary for him in the flow of information, as well as to meet their needs.